2014
DOI: 10.1002/smll.201401706
|View full text |Cite
|
Sign up to set email alerts
|

Virus Capture and Destruction by Label‐Free Graphene Oxide for Detection and Disinfection Applications

Abstract: Graphene oxide (GO) can efficiently capture viruses, destroy their surface proteins, and extract viral RNA in an aqueous environment by using the superficial bioreduction of GO. It follows from these phenomena that GO is an excellent nanomaterial for the high-throughput detection and disinfection of viruses, demonstrating its great potential for the prevention of environmental infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 43 publications
1
122
0
Order By: Relevance
“…Comparison experiments confirmed that both the negative charges and nanosheet structure contributed to their antiviral ability . It was further shown that heat treatment could enhance virus capture and even denaturation due to the excellent heat and electron transfer properties of GO or rGO …”
Section: Interactions Between Graphene Derivatives and Pathogensmentioning
confidence: 75%
See 1 more Smart Citation
“…Comparison experiments confirmed that both the negative charges and nanosheet structure contributed to their antiviral ability . It was further shown that heat treatment could enhance virus capture and even denaturation due to the excellent heat and electron transfer properties of GO or rGO …”
Section: Interactions Between Graphene Derivatives and Pathogensmentioning
confidence: 75%
“…In some other studies, it was reported that the negative charges on GO and rGO along with their unique single‐layer structure were enough to bind and thus suppress the infection of the pseudorabies virus (PRV, a DNA virus) and porcine epidemic diarrhea virus (PEDV, an RNA virus) . Comparison experiments confirmed that both the negative charges and nanosheet structure contributed to their antiviral ability . It was further shown that heat treatment could enhance virus capture and even denaturation due to the excellent heat and electron transfer properties of GO or rGO …”
Section: Interactions Between Graphene Derivatives and Pathogensmentioning
confidence: 89%
“…Vaccines are sensitive to temperature changes; thus, continuous refrigeration facilities are required to maintain their potency . However, some areas lack dependable refrigeration equipment to store and deliver vaccines, and thus, a significant portion are wasted.…”
Section: Biological Strategy For Organism Modificationmentioning
confidence: 99%
“…Many strategies have been employed to stabilize vaccines, including silk, minerals, and sugars. [175b] Among the biogenic stabilizers utilized, CaP are of interest because of their good biocompatibility and are now utilized as a transferring agent and adjuvant to stabilize vaccines. [175b] CaP shells can be introduced onto viral surfaces when the calcium ion concentration is high …”
Section: Biological Strategy For Organism Modificationmentioning
confidence: 99%
“…Notably, glycerol monolaurate prevented mucosal simian immunodeficiency virus transmission in a rhesus macaque model . While peptides and surfactants have been the main agents explored for virucidal activity and benefit from nanotechnology‐enabled formulations, several nanomaterials themselves have also been reported to destabilize enveloped viruses, including graphene oxide surfaces and silver nanoparticles as well as polymeric thin films . Collectively, there are many opportunities to incorporate membrane‐lytic agents into prophylactic strategies, especially topical and disinfectant applications, and further investigation of therapeutic strategies across the range of lipid envelope‐targeting agents is also warranted for extracellular virion impairment.…”
Section: Nanomedicine Strategiesmentioning
confidence: 99%